SARS-CoV-2 Infection Complicated by Acute Pericarditis Concurrent with Malaria Infection - Hocin, Kevin; Kusuma, Yudha; Dewi, Atit Puspitasari (Jurnal Penyakit Dalam Indonesia, 2022)
Coronavirus disease 19 (COVID-19) can present as various symptoms, which range from asymptomatic to severe symptoms. We report a case of COVID-19 female patient with malaria co-infection who developed pericarditis complication. In this pandemic era, it is mandatory to rule out COVID-19. Coinfection with malaria will result in higher cytokine levels which lead to atypical complication, such as pericarditis. Prompt identification of atypical COVID-19 complications is essential as it can lower the mortality rate and reduce the duration of hospitalization.